Interactions of 2,4,6-trinitrotoluene (TNT) with xenobiotic biotransformation system in European eel Anguilla anguilla (Linnaeus, 1758) - DELLA TORRE, CAMILLA; CORSI, ILARIA; ARUKWE A; VALOTI, MASSIMO; FOCARDI, SILVANO ETTORE (Ecotoxicology and Environmental Safety, 2008)
The aim of the present study was to investigate the interaction of 2,4,6-trinitrotoluene (TNT) with liver biotransformation enzymes in European eel Anguilla anguilla (Linnaeus, 1758). Eels were exposed to 0.5, 1 and 2.5 mg/l nominal concentrations of TNT for 6 and 24 h. Modulation of CYP1A1, UDPGT and GST genes was investigated by real-time PCR. Total CYP450 content, NADPH cytochrome c reductase activity, CYP1A and CYP2B-like activities, such as EROD, MROD and BROD, as well as GST and UDPGT activities, were measured by biochemical assays. An in vitro study was performed on EROD in order to evaluate catalytic modulation by TNT. No modulation of the CYP1A1 gene or protein was observed in TNT-exposed eels. On the other hand, a significant decline of EROD and MROD activities was observed in vivo. An increase in NADPH cyt c reductase, and phase II enzymes (UDPGT and GST) were observed at both gene expression and activity levels. The overall results indicated that TNT is a potential competitive inhibitor of CYP1A activities. A TNT metabolic pathway involving NADPH cyt c reductase and phase II enzymes is also suggested.